Media Sosial sebagai Demokrasi Partisipatif yang Potensial - Dharma Oratmangun; Udi Rusadi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
Social media gives previously silent masses an expressive voice in a possible participatory democracy. The majority of these are critiques of Henry Jenkins' writings, who is an advocate of web-based participatory democracy. Jenkins was attacked by Fuchs for minimizing participation to its cultural value and so disregarding the importance of ownership in determining the scope and mode of participation. A truly participatory democracy must also be a property democracy, as Fuchs demonstrates. A fully participatory culture must also have equity in ownership so that everyone has access to the means and visibility of cultural production and distribution.